ADAMTS13 activity, high VWF and FVIII levels in the pathogenesis of deep vein thrombosis. Issue 197 (January 2021) - Pagliari, Maria Teresa; Boscarino, Marco; Cairo, Andrea; Mancini, Ilaria; Martinelli, Ida; Bucciarelli, Paolo; Rossi, Federica; Rosendaal, Frits R.; Peyvandi, Flora
Abstract: Background: Deep vein thrombosis (DVT) is a common multi-factorial disease with a partially understood aetiology. Although the roles of high factor (F)VIII and von Willebrand factor (VWF) levels are recognized, that of ADAMTS13 is still unclear. Aim: To assess the association between ADAMTS13 activity levels, VWF antigen (VWF:Ag) and FVIII coagulant activity (FVIII:C) levels and DVT. Materials and methods: 365 Italian DVT patients and 292 age- and sex-matched controls were considered. Plasma ADAMTS13 activity was measured using FRETS-VWF73 assay. VWF:Ag and FVIII:C were measured using immunoassay and one-stage clotting assay (ACL TOP analyzer), respectively. Quartile analyses were performed to evaluate the individual association between ADAMTS13 activity, VWF:Ag, FVIII:C and DVT. The combined effect of high VWF levels (> 4th quartile) and low ADAMTS13 levels (< 1st quartile) was evaluated using binary variables. All models were age- and sex-adjusted. Estimated risks were reported as Odds ratio (OR) with 95% confidence intervals (CI). Results: ADAMTS13 activity was lower in DVT patients (94% vs. 98% of controls). Patients with an ADAMTS13 activity <1st quartile (86%) showed a 1.6-fold increased risk of DVT (95%CI, 1.05–2.55). The combination of low ADAMTS13 activity and high VWF:Ag levels was associated with a 15–fold increased risk (95%CI, 7.80–33.80). VWF:Ag and FVIII:C were associated to DVT with a dose-response relationship. Conclusions: ADAMTS13 activity < 86% was associated with a moderate risk of DVT. The co-presence of low ADAMTS13 activity and high VWF levels resulted in a strong synergistic effect on DVT risk. The association of VWF:Ag and FVIII:C with DVT was confirmed. Highlights: Deep vein thrombosis (DVT) aetiology is partially understood. We evaluated the association of ADAMTS13 activity, VWF:Ag, FVIII:C levels and DVT. Low ADAMTS13 activity levels alone or combined with high VWF level increase DVT risk. We confirmed the association of high VWF:Ag and FVIII:C levels and DVT.